The German stock market : its operations, problems, and prospects - Baker, James Calvin (New York : Praeger, 1970)
This book provides a complete, up-to-date description of the organized securities exchange in Germany, with emphasis upon their equity markets.
Bibliography: p. [177]-195.
osc 02/08/2018
Loans
Keywords: Stock exchanges